Partnerships and Coalition Building for Advocacy - Breny, Jean M.; De Leon, Breanna; Schwartz, Elizabeth J. (Be the Change: Putting Health Advocacy, Policy, and Community Organization into Practice in Public Health Education, 2023)
The information and skills build to Chapter 10, where the work of a grassroots organization was investigated and how that work coincides with other advocacy and policy issues. Grassroots advocacy is a specific form of advocacy that starts from the roots (i.e., from the community itself) and grows upward from there. This is where the advocate deepens their knowledge about partnership building and collaboration and how it serves the profession to further the development of changes needed. Professional organizations and associations become important to the advocacy efforts at this level, and how to work together on the issues is shared.
Keywords: dept.pch